Management Accounting Systems Change and Departmental Performance: The Influence of Managerial Information and Task Uncertainty - Williams, John Joseph (Institutional Knowledge at Singapore Management University, 2002)
Despite the proliferation of new management accounting techniques amidst pressures of organizational and global change, the issue of changes in firm-wide management accounting and control systems (MACSs) has largely been ignored in the research literature. This study explores the indirect effect of MACSs change on departmental performance for a cross-sectional sample of 232 medium-sized Singaporean firms. It is hypothesized that MACSs change affects performance but not directly. Instead, this relationship is mediated by managerial-relevant information (MRI) that is impacted by MACSs change, which, in turn, enhances performance. Task uncertainty is expected to moderate the intervening linkages; specifically, the latter are anticipated to strengthen under conditions of more task variability and task difficulty and, thus, augment the indirect effect of MACSs change on performance. The results offer support for the positive indirect effect of improving departmental performance from more MRI, triggered by MACSs change. Although not large, the indirect effect is strengthened when task variability and task difficulty are high. Overall, the findings are consistent with the stated purposes of management accounting that are embedded in normative definitions, and which are relied upon to motivate the framework for analysis.